Correlation between Learning Comfort and the Risk of Musculoskeletal Disorder in Anatomy Laboratorium Activity Based on RULA Method - Lubis, Leonardo; Putri, Jesslyn Christianningrum; Ardisasmita, Mulya Nurmansyah (International Journal of Integrated Health Sciences, 2019)
Objective: To describe learning comfort in the anatomy class of the Faculty of Medicine, Universitas Padjadjaran as one of the learning facilities, to assess the risk of musculoskeletal disorders in students, and to observe correlation between learning comfort and the risk of musculoskeletal disorders in students. Method: A cross sectional research design conducted to the participants that were students from batch 2017 (second year), faculty of Medicine, Universitas Padjadjaran as the population sample. Data were taken using a Likert scale questionnaire (very uncomfortable–very comfortable) about the comfort aspects in the class, meanwhile the risk of musculoskeletal disorders were assessed by using Rapid Upper Limb Assessment (RULA). After data collection, there were 106 respondents with complete data, then the data were processed by using descriptive statistical analyses. The correlation between the two variables was analyzed using the Gamma correlation test.Results: Majority of the students were very comfortable with the aspects of learning comfort (majority scale 5), except in aspects of furniture, work area, room aroma, personal storage area, maintenance and repair. A moderate risk level of musculoskeletal disorders (58.5%) was found in the majority of the students. There was a relative significant relationship between learning comfort and the risk of musculoskeletal disorders in the aspect of colors (γ=0.445, p<0.01).Conclusion: There is a significant relationship between learning comfort in the aspect of colors and the risk of musculoskeletal disorders. Other aspects do not indicate a significant relationship.Keywords: Learning comfort, risk of musculoskeletal disorders, RULA